PENERAPAN REFLEKSI PRIBADI UNTUK MEMBANTU GURU MENJALANKAN PERAN SEBAGAI FASILITATOR PADA PEMBELAJARAN DARING - Vinny Yuniar Ranasiwi Seco; Wiputra Cendana (Institut Agama Hindu Negeri Gde Pudja Mataram, 2022)
Teachers as a facilitator is who facilitates students' needs to reflect on learning based on Biblical truth. The fact that happened in one of the Christian schools in Tangerang, there are a problem while teacher facilitating students in online learning. Therefore, teachers need to implement appropriate solutions to improve them. This paper aims to examine whether teacher personal reflection can assist teachers in carrying out their role as facilitators, which aims to find out the importance of personal reflection to help teachers as facilitators carry out their role in online learning. The method of writing uses descriptive qualitative. Personal reflection is a response to our salvation which is part of progressive sanctification to become more like Christ. Biblical truth is the basis for teachers' belief in reflection. As a result, through the implementation of personal reflection, teachers can find out problems then find solutions to correct mistakes when facilitating students in online learning. The conclusion is that the application of teacher personal reflection helps teachers to carry out their role as facilitators in online learning. The next writer is advised to use feedback from students to be the source of reflection